Strategi Mitigasi Resiko Supply Chain Dengan Metode House of Risk - Eko Wahyu Abryandoko; Mushthofa Mushthofa (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2020)
CV. Asri Tehnika is a company engaged in the construction, one of the projects that is now in the work by CV. Asri Tehnika is a project building construction of SDN Tlogoagung in Bojonegoro district. This research aims to identify various risks that occur in CV. Asri Tehnika at the time of construction of the building of SDN Tlogoagung District Kedungadem District Bojonegoro, along with the cause. The method used in this research is House of Risk, this method consists of two phases, namely the first phase to identify risk and risk agent, while the second phase is risk management. This research is expected to assist in the problem of supply chain activities within the company.